Heaven it's my wife! Male canaries conceal extra-pair courtships but increase aggressions when their mate watches. - Davy Ung; Mathieu Amy; Gérard Leboucher (PLoS ONE, 2011)
Many animals live in a communication network, an environment where individuals can obtain information about competitors or potential mates by observing interactions between conspecifics. In such an environment, interactants might benefit by changing their signalling behaviour in the presence of an audience. This audience effect seems widespread among species, has been observed during various types of interaction (e.g. intra-sexual vs. inter-sexual interaction) and varies according to the social context (e.g. gender, hierarchical or mating status of the audience). However, the way individuals might adapt their signalling behaviour to a combination of these factors remains poorly understood. To address this question, we studied how the presence of an audience affects the behaviour of male domestic canaries Serinus canaria during two types of interactions: (i) an extra-pair interaction and (ii) a male-male competition for food. Males were observed under three conditions: (a) in the absence of audience, (b) in the presence of their mate or (c) of a familiar female. Our results show that male domestic canaries minutely adapt their courting and agonistic behaviours to a combination of: (i) the type of interaction (extra-pair interaction/male-male competition), (ii) the social context (mate, familiar female or nobody in audience) and (iii) the behaviours of both the audience and the interactant. These results highlight the ability of animals to subtly adapt their behaviour to the social environment. This also raises questions about the cognitive foundations and evolution of these processes especially considering that canaries are known neither for having high cognitive abilities nor for being a typical example for the social intelligence hypothesis.